Implementation of the Legality Principle in the Criminal Justice System of Indonesia - AMIR, Firman; MEIFANI, Marina Tresna Ayu; SATRIADI; SETIYONO, Aries; MIKO; KRISTHY, Mutia Evi (Indonesia Strategic Sustainability, 2023)
Purpose:The legality principle, a fundamental concept in Indonesian criminal law, underpins the legal framework for societal order. Originating from historical roots, it ensures justice, human rights protection, and transparent law enforcement. Article 1 Paragraph 1 of the Criminal Code solidifies its significance in Indonesian positive law. By examining the historical evolution, implications, and challenges of the legality principle, this article aims to deepen the comprehension of its impact on Indonesian criminal law. The ultimate goal is to contribute to a just and effective judicial system.Methodology:This study employs standard research methods, including a legal literature review and analysis of court decisions, to explore the application of the legality principle in the Indonesian criminal justice system.Findings:The principle enshrined in Article 1 Paragraph (1) of the Criminal Code emphasizes that punishment must align with pre-existing laws. It prohibits retroactive application and analogy use and ensures adherence to formal legal principles. In the Indonesian context, the legality principle is crucial for protecting citizens' rights, maintaining justice, and upholding societal values. Its application intersects with legal concepts like